The impact of air quality index (AQI) and particulate matter 2.5 (PM) concentration on the incidence of stroke in Karachi, Pakistan: a bidirectional cohort study - Ali, Malaika; Saba Zaidi; Kazi, Harris Iqbal; Shahab, Farhan (Journal of the Pakistan Medical Association, 2026)
Objective: To investigate the association between air pollution and the incidence of ischemic and hemorrhagic strokes. Method: The bidirectional cohort study was conducted at the Neurology Department of Liaquat National Hospital, Karachi, from August 10, 2022, to February 5, 2024, and comprised newly hospitalised patients who experienced an acute onset of stroke, including both ischemic and haemorrhagic types. Precise documentation of stroke onset dates and times was done. Air pollutant data, specifically the Air Quality Index and particulate matter 2.5 concentrations, was sourced from the relevant Swiss website, which provides extensive real-time and historical air quality measurements. For each patient, air quality data was collected for the three days preceding the stroke onset. The association between stroke type and exposure variables was explored, and the odds of stroke occurrence in relation to particulate matter 2.5 exposure were worked out. Data was analysed using SPSS version 27. Results: Of the 228 patients,149(65.4%) were males and 79(34.6%) were females. The overall mean age was 62.15±14.20 years. Stroke subtype and onset time had no significant association with air quality index readings or or with particulate matter 2.5 at days 1, 2 and 3 (p>0.05). Males exhibited a heightened propensity for experiencing ischemic strokes compared to females (odds ratio: 1.179, p=0.606). Moreover, individuals afflicted with ischemic heart disease demonstrated an elevated risk of suffering ischemic strokes compared to those without the comorbidity (odds ratio: 2.986, p=0.051). Conclusion: Short-term rise in air quality index readings and particulate matter 2.5 concentrations were found to have no association with the incidence of ischemic and hemorrhagic strokes. Key Words: Ischemic stroke, Haemorrhagic stroke, Air Quality Index, Particulate matter, Air pollution, Environmental exposure.